Exploring the predictive influence of licensure examination results for beginning teachers’ performance: the case of the Philippines - Cadosales, Maria Nancy Q.; Sanchez, Joje Mar P.; Cordova, Monique E.; Merin, Jewish A.; Augusto, William S. (Frontiers in Education, 2023)
Passing the Board Licensure Examination for Professional Teachers (BLEPT) is a major requirement for graduates to be accepted to teach in the Department of Education (DepEd). The holistic preparation of these teachers determines how well they perform in the field. This study investigated the relationship between the beginning teachers' performance in the licensure examination and their results-based performance management system rating. The descriptive-correlational research design was used in this study. The data were systematically obtained from 2,680 teachers representing the 17 regions in the Philippines through a researcher-made survey instrument administered online from May to July 2022. Means and standard deviations described the BLET and RPMS performances. At the same time, hierarchical regression, path, and effect analyses were used to determine the impact of BLET performance, teaching experience, and college preparation on teaching performance. The beginning teachers with BEEd, BSEd, and DPE degrees received satisfactory BLEPT performance and a very satisfactory RPMS performance. Furthermore, the performance in General Education, Professional Education, and Specialization components predicted the RPMS performance of teachers who graduated from the BSEd degree program. College preparation impacted RPMS performance, while teaching experience in private and public schools showed different impacts in their teaching. Finally, the findings of this study show that the BLET performance of teachers impacts the RPMS ratings; hence, licensure exam results can predict teachers' performance in public schools. The quality of teacher preparation influences the preservice teachers' performance in the board licensure examination for professional teachers. Hence, it is recommended that teacher education institutions intensify their measures in preparing preservice teachers to pass the board licensure examination for professional teachers.